Surface adsorption behaviour of milk whey protein and pectin mixtures under conditions of air-water interface saturation - Perez, Adrián Alejandro (2011)
Milk whey proteins (MWP) and pectins (Ps) are biopolymer ingredients commonly used in the manufacture of colloidal food products. Therefore, knowledge of the interfacial characteristics of these biopolymers and their mixtures is very important for the design of food dispersion formulations (foams and/or emulsions). In this paper, we examine the adsorption and surface dilatational behavior of MWP/Ps systems under conditions in which biopolymers can saturate the air–water interface on their own. Experiments were performed at constant temperature (20 ºC), pH 7 and ionic strength 0.05M. Two MWP samples, beta-lactoglobulin ( beta-LG) and whey protein concentrate (WPC), and two Ps samples, low-methoxyl pectin (LMP) and high-methoxyl pectin (HMP) were evaluated. The contribution of biopolymers (MWP and Ps) to the interfacial properties of mixed systems was evaluated on the basis of their individual surface molecular characteristics. Biopolymer bulk concentration capable of saturating the air–water interface was estimated from surface pressure isotherms. Under conditions of interfacial saturation, dynamic adsorption behavior (surface pressure and dilatational rheological characteristics) of MWP/Ps systems was discussed from a kinetic point of view, in terms of molecular diffusion, penetration and configuration al rearrangement at the air–water interface. The main adsorption mechanism in MWP/LMP mixtures might be the MWP interfacial segregation due to the thermodynamic incompatibility between MWP and LMP (synergistic mechanism); while the interfacial adsorption in MWP/HMP mixtures could be characterized by a competitive mechanism between MWP and HMP at the air–water interface (antagonis- tic mechanism). The magnitude of these phenomena could be closely related to differences in molecular composition and/or aggregation state of MWP ( beta-LG and WPC).